2021
DOI: 10.3390/su13137275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Social Distancing Policies on Traffic Congestion, Mobility, and NO2 Pollution

Abstract: Lockdowns implemented during the COVID-19 pandemic were utilized to evaluate the associations between “social distancing policies” (SDPs), traffic congestion, mobility, and NO2 air pollution. Spatiotemporal linear mixed models were used on city-day data from 22 US cities to estimate the associations between SDPs, traffic congestion and mobility. Autoregressive integrated moving average models with Fourier terms were then used on historical data to forecast expected 2020 NO2. Time series models were subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…The positive impact of the pandemic on the environment has evidenced from the better air quality due to the reduction of economic activities worldwide, supporting the progress toward SDG 13 for climate change. The recent research also supports the positive impact [19,40,49]. As economic production temporarily stopped, the emission of greenhouse gas and aerosols decreased.…”
Section: Environmental Dimensionmentioning
confidence: 62%
See 2 more Smart Citations
“…The positive impact of the pandemic on the environment has evidenced from the better air quality due to the reduction of economic activities worldwide, supporting the progress toward SDG 13 for climate change. The recent research also supports the positive impact [19,40,49]. As economic production temporarily stopped, the emission of greenhouse gas and aerosols decreased.…”
Section: Environmental Dimensionmentioning
confidence: 62%
“…The review table also shows that their research results and discussions are dispersed with diverse contextual applications. The review also identifies various articles with emphasis on different sustainability pillars (i.e., economic, environmental and social dimensions [9,13,19]. Additionally, only few studies analyze the pandemic effects on all three sustainability pillars, based on the holistic framework of the UN SDGs [7,8,10,14].…”
Section: Overview Of Covid-19 Impacts On Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A noticeable effect on air pollution was observed, and it is discussed that policies implemented for COVID-19 spread reduction could also be implemented for the purpose of air pollution improvement. The research in [11] observed reductions in congestion, mobility, and NO 2 during the lockdown across 22 US cities using regression models. The research was also conducted in smaller cities, as reported in [12], where the city of Maribor, Slovenia, was observed during COVID-19 lockdowns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, in Singapore a 54% NO 2 concentration reduction which is significantly correlated (Spearman) to human mobility reduction [47]. On the other hand, a worldwide study has described a maximum of 70% NO 2 Air Quality Index (AQI) reduction observed in the Philippines, seconded by Lima, Perú with a 55% and reaching a 60% mobility reduction across Europe, Asia, and the Americas [48, 49].…”
Section: Introductionmentioning
confidence: 99%